A predictive and moderation model of depression in adolescents, and the creation of the Javier-Aliaga’s single-item scales of happiness and self-efficacy (version 1.0) - David Javier-Aliaga; José Anicama; Yaquelin E. Calizaya-Milla; Jacksaint Saintila (BMC Psychology)
Abstract Background The high prevalence of depression among adolescents highlights the need for research aimed at identifying variables with predictive capacity for this condition. In parallel, the scarcity of single-item scales assessing happiness and self-efficacy underscores the importance of developing validated instruments tailored to the Peruvian context. This study aims to examine the predictive roles of perfectionism, self-efficacy, and happiness on depression, as well as the moderating role of sex among Peruvian adolescents. Additionally, it proposes the development of two new instruments: the Javier-Aliaga’s Single-Item Scale of Happiness and the Single-Item Scale of Self-Efficacy. Methods A cross-sectional predictive study was conducted in 380 adolescents from a public school in Lima, Peru, of whom 50.3% were male and Mage = 13.9 (SD = 1.16). The Reynolds Adolescent Depression Scale (RADS-2), the 6-item Perfectionism Scale (EDI-P6), the Javier-Aliaga’s Single-Item Scale of Happiness (JASIHS-v1.0) and the Single-Item Scale of Self-Efficacy (JASISS-v1.0) were used. Predictive analysis was performed using multiple linear regression. Results The multiple regression analysis showed that Model 2 was the most appropriate (F = 128, p < 0.001, BIC = 2878). The variables perfectionism (β = 0.283, CI [0.215, 0.351], p < 0.001), self-efficacy (β = -0.236, CI [-0.312, -0.161], p < 0.001), happiness (β = -0.386, CI [-0.463, -0.309], p < 0.001), and sex (β = 0.239, CI [0.170, 0.307], p < 0.001) explained 57.3% of the variability in depression (adjusted R2 = 0.573), with happiness being the most influential variable (β = -0.386). The moderation analysis revealed that sex significantly moderated the relationships between perfectionism (b = 0.713, CI [0.166, 1.260], p = 0.011), self-efficacy (b = -3.845, CI [-6.097, -1.593], p = 0.001), and happiness (b = -3.750, CI [-6.134, -1.367], p = 0.002) with depression, with these interactions being stronger in females. Additionally, the JASISS-v1.0 and JASIHS-v1.0 demonstrated excellent content validity (Aiken’s V = 1.00; M = 3.00; SD = 0; 95% CI = 0.70–1.00) and acceptable test–retest reliability (0.71 for the JASISS-v1.0 and 0.76 for the JASIHS-v1.0). Conclusion The findings highlight the significant influence of perfectionism, self-efficacy, and happiness on depression among Peruvian adolescents, with happiness emerging as the most impactful variable. Moreover, the moderating role of sex suggests that interventions targeting these factors should be designed differently for males and females. Additionally, the development and validation of the JASIHS-v1.0 and the JASISS-v1.0 represent a valuable contribution by providing brief, culturally relevant, and psychometrically sound instruments.